Implementation Implementation of Free Health Check-up Policy for The Community in Samarinda City - Budy Setyawan; Enos Paselle; Kus Indarto (PUBLIKA : Jurnal Ilmu Administrasi Publik, 2026)
This study analyzes the implementation of the Free Health Examination (PKG) policy in Samarinda City based on the Decree of the Minister of Health Number HK.01.07/MENKES/33/2025 and identifies the factors hindering its implementation. A descriptive qualitative approach was employed using in-depth interviews, observations, and documentation. Sixteen purposively selected informants included officials from the Health Office, heads of health centers, technical staff, community members, and health cadres. Data were analyzed using the Miles and Huberman interactive model and the Van Meter and Van Horn policy implementation framework. The findings indicate that PKG implementation remains suboptimal. Only 45,590 of the 822,962 targeted beneficiaries (15.66%) had received services, with considerable disparities among health centers (0.75–12.64%). Major barriers include inconsistent understanding of policy standards, limited budgets (covering only about 43% of estimated needs), shortages of health personnel, inconsistent adherence to standard operating procedures, weak cross-sector coordination, inadequate public outreach, declining implementation motivation, and the continued dominance of a curative healthcare paradigm. Leadership commitment among health center heads emerged as the key factor distinguishing high- and low-performing facilities. The study recommends developing local technical guidelines, increasing budget allocation, strengthening cross-sector collaboration, and adopting community-based, face-to-face socialization strategies to improve policy implementation.